PECALANG: DINAMIKA KONTESTASI KEKUASAAN DI BALI - Gede Indra Pramana (Universitas Airlangga, 2012)
Discussions on Bali today are dominated by the hustle and bustle of tourism. Bali is often depicted asexclusive territory free from politics. Therefore, readings about Bali are commonly analysed in thecontext of tourism development. This article tries to show that Bali is not merely an exotic paradise.By reviewing pecalang, the guardian of traditional customs in Bali, it will be shown that powerstruggles take place in the meaning of pecalang. The genealogy of power in Bali also shows thatpower is truly embedded in the everyday life of the Balinese.